Intelligent Supply Chain Integration and Management Based on Cloud of Things. (16th March 2014) - Yan, Junwei; Xin, Sijin; Liu, Quan; Xu, Wenjun; Yang, Liwen; Fan, Li; Chen, Bo; Wang, Qiang
The fierce global competition and market turbulence has been forcing the enterprises towards to the integration and intelligence for supply chain management, and the seamless information sharing and collaboration as well as operation agility are the challenges which need to be conquered, in terms of the highly distributed and heterogeneous resources located in separated warehouses. Although a number of works have been done to achieve the aforementioned targets, few of them are able to provide an overall integration and intelligence support for such system management. In this context, a novel intelligent supply chain integration and management system based on Cloud of Things is presented, in order to provide flexible and agile approaches to facilitate the resource sharing and participant collaboration in the whole supply chain life cycle. Furthermore, the enabling technologies, such as intelligent supply chain condition perception, heterogeneous network access convergence, and resource servicisation, are also studied. Finally, a case study together with the prototype system is implemented and demonstrates that the developed system can efficiently realise the integration of supply chain processes in the form of services, and also provide the effective intelligence support for physical resource management, so as to achieve an overall performance assurance for the system operation.